Competition policy and patent law under uncertainty regulating innovation - Manne, Geoffrey A.; Wright, Joshua D.; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2011)
"The regulation of innovation and the optimal design of legal institutions in an environment of uncertainty are two of the most important policy challenges of the twenty-first century. Innovation is critical to economic growth. Regulatory design decisions, and, in particular, competition policy and intellectual property regimes, can have profound consequences for economic growth. However, remarkably little is known about the relationship between innovation, competition, and regulatory policy. Any legal regime must attempt to assess the tradeoffs associated with rules that will affect incentives to innovate, allocative efficiency, competition, and freedom of economic actors to commercialize the fruits of their innovative labors. The essays in this book approach this critical set of problems from an economic perspective, relying on the tools of microeconomics, quantitative analysis, and comparative institutional analysis to explore and begin to provide answers to the myriad challenges facing policymakers" -- Provided by publisher
Introduction; Part I. Keynotes: 1. Information, capital markets, and planned development: an essay Robert Cooter; 2. The disintegration of intellectual property Richard A. Epstein; Part II. The Economics of Innovation: 3. Regulation of bundling in standards and new technologies Stan J. Liebowitz and Stephen E. Margolis; 4. Unlocking technology: antitrust and innovation Daniel F. Spulber; 5. Creative construction: assimilation, specialization, and the technology life cycle Marco Iansiti and Greg Richards; Part III. Innovation and Competition Policy: 6. Favoring dynamic over static competition: implications for antitrust analysis and policy David Teece; 7. Antitrust, multi-dimensional competition, and innovation: do we have an antitrust-relevant theory of competition now? Joshua D. Wright; 8. Section 2 and article 82: a comparison of American and European approaches to monopolization law Keith N. Hylton and Haizhen Lee; Part IV. The Patent System: 9. Rewarding innovation efficiently: the case for exclusive rights Vincenzo Denicol- and Luigi Alberto Franzoni; 10. Presume nothing: rethinking patent law's presumption of validity Mark Lemley and Douglas G. Lichtman; 11. Patent notice and patent design Michael Meurer; Part V. Property Rights and the Theory of Patent Law: 12. Commercializing property rights in inventions: lessons for modern patent theory from classic patent doctrine Adam Mossoff; 13. Modularity rules: information flow in organizations, property, and intellectual property Henry Smith; 14. Removing the property from intellectual property and (intended?) pernicious impacts on innovation and competition F. Scott Kieff; Part VI. Intellectual Property and Antitrust: The Regulations of Standard Setting Organizations: 15. Increments and incentives: the dynamic innovation implications of licensing patents under an incremental value rule Anne Layne-Farrar, Gerard Llobet, and Jorge Padilla; 16. What's wrong with royalty rates in high technology industries? Damien Geradin; 17. Federalism, substantive preemption, and limits on antitrust: an application to patent holdup Bruce H. Kobayashi and Joshua D. Wright
Title from title screen (viewed on November 15, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Patent laws and legislation; Competition, Unfair; Technological innovations -- Law and legislation; Antitrust law